Criminal Liability for Phishing Perpetrators: A Normative Analysis of Indonesian Criminal Law - Prasetyo Wisnu Langgono; Hartoyo Hartoyo; Fitri Ayuningtyas (International Journal of Law and Society, 2026)
Phishing constitutes a form of cybercrime that continues to proliferate alongside the rapid advancement of information technology, causing significant impacts on data security and financial losses. This study aims to analyse the forms of criminal liability applicable to phishing perpetrators under Indonesian criminal law and to identify the challenges and solutions in its enforcement. The research employs a normative juridical approach utilising literature review methodology. The findings demonstrate that criminal liability for phishing perpetrators can be established through provisions in the Electronic Information and Transactions Law (ITE Law) as amended by Law Number 1 of 2024, the Indonesian Penal Code (KUHP), and related regulations. However, law enforcement faces numerous obstacles, including inadequate specific legal regulations, limited digital forensic technology, low public legal literacy, and cross-border jurisdictional barriers. In judicial proceedings, evidentiary processes are frequently hindered by the complexity of electronic evidence and the limited technical understanding among law enforcement officers. This study recommends regulatory reform, capacity building for human resources, international cooperation, and public education to strengthen the effectiveness of law enforcement against phishing crimes.